Distinct Failure Patterns in Hypopharyngeal Cancer Patients Receiving Surgery-Based Versus Radiation-Based Treatment - Lin, Yu-Hsuan; Hsiao, Jenn-Ren; Wu, Yuan-Hua; Chang, Jeffrey S.; Ou, Chun-Yen; Lee, Wei-Ting; Huang, Cheng-Chih; Chang, Chan-Chi; Lai, Yu-Hsuan; Tsai, Sen-Tien; Hsueh, Wei-Ting; Yen, Chia-Jui; et al. (Annals of surgical oncology, 2023)
Background To cure advanced hypopharyngeal squamous cell carcinoma (HPSCC), primary operation followed by adjuvant (chemo-)radiotherapy (OP-CRT) or definitive chemoradiation (CCRT) are the two primary options. This study aimed to compare the failure patterns and long-term survival outcomes of HPSCC patients treated with these two strategies. Patients and Methods From 2007 to 2015, 198 pathologically confirmed HPSCC patients receiving either OP-CRT or CCRT were retrospectively reviewed. Failure patterns and survival outcomes stratified by the 7th American Joint Committee on Cancer staging system and treatment modalities were compared. Results One hundred and eighty-nine patients (95.4%) were stage III/IV and 62 patients (31.3%) received OP-CRT. Median follow-up duration was 4.9 years. Compared with CCRT, OP-CRT provided better 3-year local relapse-free survival for T3 (93 vs 48%, p < 0.0001), T4a (88 vs 37%, p = 0.0005) and better 3-year regional relapse-free survival for N2b+2c (93 vs 60%, p < 0.0001). Of note, for stage IVA subjects, OP-CRT provided better 3-year loco-regional relapse-free survival (85 vs 37%, p < 0.0001), marginal poor 3-year distant metastasis-free survival (62 vs 79%, p = 0.06), but comparable 3-year OS (52 vs 44%, p = 0.37) and 5-year OS (44 vs 31%, p = 0.15) compared with CCRT. Conclusions For patients with advanced HPSCC, although OP-CRT and CCRT provided similar overall survival, failure patterns were distinct. OP-CRT provided better loco-regional control but was more likely to encounter distant metastases than CCRT. The detailed analysis of failure patterns will pave the way to improve this devastating disease.